4(z+2)-7z=6(-0.5z+1)+2

Simple and best practice solution for 4(z+2)-7z=6(-0.5z+1)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(z+2)-7z=6(-0.5z+1)+2 equation:


Simplifying
4(z + 2) + -7z = 6(-0.5z + 1) + 2

Reorder the terms:
4(2 + z) + -7z = 6(-0.5z + 1) + 2
(2 * 4 + z * 4) + -7z = 6(-0.5z + 1) + 2
(8 + 4z) + -7z = 6(-0.5z + 1) + 2

Combine like terms: 4z + -7z = -3z
8 + -3z = 6(-0.5z + 1) + 2

Reorder the terms:
8 + -3z = 6(1 + -0.5z) + 2
8 + -3z = (1 * 6 + -0.5z * 6) + 2
8 + -3z = (6 + -3z) + 2

Reorder the terms:
8 + -3z = 6 + 2 + -3z

Combine like terms: 6 + 2 = 8
8 + -3z = 8 + -3z

Add '-8' to each side of the equation.
8 + -8 + -3z = 8 + -8 + -3z

Combine like terms: 8 + -8 = 0
0 + -3z = 8 + -8 + -3z
-3z = 8 + -8 + -3z

Combine like terms: 8 + -8 = 0
-3z = 0 + -3z
-3z = -3z

Add '3z' to each side of the equation.
-3z + 3z = -3z + 3z

Combine like terms: -3z + 3z = 0
0 = -3z + 3z

Combine like terms: -3z + 3z = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 5(5c-1)-1=20c+4 | | 4-3[q]=10 | | 65(2x-5)=180 | | Cos(45+x)=.42cos(45-x) | | 8(4-2.5)=16 | | 11(-3x+2)-2(1-5x)=-7x-6x | | 9(4-2n)-3=4-6(3n-5) | | 3ln(x+2)-5ln(5x)=x | | .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) | | 3x^2-36x-27=0 | | 4m+4+7m=13+8m | | 11(-3x-2)-2(1-5x)=-7x-6x | | 5345+n=288195 | | m+3(4)=7 | | F(-3)=2x+4 | | .66m+2=1m-3 | | 53435+n=2888195 |

Equations solver categories